Effects of the extraordinary measures implemented by Banco de México during the COVID-19 pandemic on financial conditions - Carlos Alba; Gabriel Cuadra; Raúl Ibarra-Ramírez (Banco de México, 2023)
This paper analyzes the effects of the extraordinary measures implemented by the Bank of Mexico during the COVID-19 pandemic on financial conditions. For this purpose, we estimate a factoraugmented vector autoregressive (FAVAR) model for the period 2001-2021. Based on this model, we construct a financial conditions index, estimate the response of this indicator and its components from a shock to the outstanding amount of these measures, and conduct a counterfactual exercise to further analyze the effect of the aforementioned measures. The results indicate that the extraordinary measures seem to have contributed to improve financial conditions. In particular, we find that if these measures had not been implemented, the sovereign risk premium, the 10-year government bond yield, the slope of the yield curve, the long and short-term yield spreads between Mexico and USA, the exchange rate and its volatility would have been higher. In turn, the Mexican stock market index would have been lower.
Keywords: C32; E58; G01; E44; 330; Financial Conditions; Central Bank Policies; Factor-Augmented VAR